A Balanced Scorecard for Maximizing Data Performance - Pierce, Elizabeth (Frontiers in Big Data, 2022)
In this study we surveyed the practitioners’ data governance/chief data officer literature for performance measurements associated with data utilization and performance. The results of this review were compiled into a scorecard to assess how well organizations are achieving the full value of their data assets. The framework for this data-focused scorecard is inspired by the classic balanced scorecard first articulated by Robert S. Kaplan and David P. Norton in the early 1990’s.